2019
DOI: 10.1002/wcs.1504
|View full text |Cite
|
Sign up to set email alerts
|

Self‐control in crows, parrots and nonhuman primates

Abstract: Self-control is critical for both humans and nonhuman animals because it underlies complex cognitive abilities, such as decision-making and future planning, enabling goal-directed behavior. For instance, it is positively associated with social competence and life success measures in humans. We present the first review of delay of gratification as a measure of self-control in nonhuman primates, corvids (crow family) and psittacines (parrot order): disparate groups that show comparable advanced cognitive abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 117 publications
(171 reference statements)
2
65
0
9
Order By: Relevance
“…The ability to forgo an immediate reward for a delayed one has been found in various nonhuman animals, including primates and birds-see [17] for a recent review of self-control in crows, parrots and non-human primates-though has primarily been tested in non-tool-using contexts. To date, no clear comparisons can be drawn between the self-control abilities of toolusing and non-tool-using species, also based on the fact that different methodologies have been used for different species.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to forgo an immediate reward for a delayed one has been found in various nonhuman animals, including primates and birds-see [17] for a recent review of self-control in crows, parrots and non-human primates-though has primarily been tested in non-tool-using contexts. To date, no clear comparisons can be drawn between the self-control abilities of toolusing and non-tool-using species, also based on the fact that different methodologies have been used for different species.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent decision-making is also important for other animals in a variety of social and foraging contexts, including inhibiting approaching food or mates in the presence of a competitor, or during tool use. Previous non-human studies have indicated large diversity of responses within the same species, see a recent review of delay of gratification in corvids (members of the crow family), parrots and non-human primates in Miller et al (2019), so self-control does not appear to be shared equally between all species or individuals. In children (Mischel et al 1972(Mischel et al , 1989 and chimpanzees (Pan troglodytes: Beran and Hopkins 2018), delay of gratification links to measures of general intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…In these tasks, subjects are required to choose between two reward options, one available immediately and one following a delay (delay choice tasks) or required to sustain the decision to delay gratification while the immediate reward is present or already possessed during the delay (delay maintenance tasks) (Ainslie 1974;Beran and Evans 2006;Tobin et al 1993Tobin et al , 1996. Subjects may be required to tolerate delays from seconds to minutes (Miller et al 2019). In the exchange paradigm, subjects may be required to swap rewards or tokens with an experimenter or conspecific to acquire the 'better' reward (Beran et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high childhood self-control has been suggested to predict positive outcomes later in life, e.g. in the context of social and academic competence [12], resilience [13], mental health [14], and physical health, financial wealth, and criminal activity [15]. A recent replication of the famous marshmallow test, however, challenged the direct link between delay of gratification performance as a child and achievements later in life.…”
Section: Introductionmentioning
confidence: 99%